2013
DOI: 10.1115/1.4025046
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Evaluation on Curved Boundaries in Thermal Lattice Boltzmann Equation Method

Abstract: An efficient and accurate approaehfor heat transfer evaluation on curved boundaries is proposed in the thermal lattice Boltzmann equation (TLBE) method. The boundary heat fluxes in the discrete velocity direetions of the TLBE model are obtained using the given thermal boundary condition and the temperature distribution functions at the lattiee nodes close to the boundaiy. Integration of the diserete boundary heat fluxes with effective surface areas gives the heat flow rate across the boundary. For lattice mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 53 publications
4
25
0
Order By: Relevance
“…For each of the three L 2 -norm errors, the minimum error occurs at different D values. The error behavior is consistent with previous findings in [27,28]. Similar trends are observed for the E 2_tint and E 2_qint values obtained from Domain 2 and using other interface and boundary schemes; thus they are not shown for brevity.…”
Section: One-d Steady Diffusion In a Horizontal Slab With Sourcessupporting
confidence: 90%
See 1 more Smart Citation
“…For each of the three L 2 -norm errors, the minimum error occurs at different D values. The error behavior is consistent with previous findings in [27,28]. Similar trends are observed for the E 2_tint and E 2_qint values obtained from Domain 2 and using other interface and boundary schemes; thus they are not shown for brevity.…”
Section: One-d Steady Diffusion In a Horizontal Slab With Sourcessupporting
confidence: 90%
“…The first-order accurate interfacial fluxes in Fig. 22 is consistent with the first-order interfacial fluxes in [30] and the first-order boundary fluxes in [27][28][29]32] for curved boundaries.…”
Section: Two-d Steady Diffusion In a Circular Domain With Interfacialsupporting
confidence: 79%
“…Similarly, the interpolated Neumann treatment using the same populations is D2Q5: 19b) For the D2Q5 model, the asymptotic analysis in [24] showed that the coefficients c n1 -c n4 in Eq. As emphasized in [24,33], when the local boundary normal n is aligned with e  (  (see Fig. 2).…”
Section: Neumann Condition Treatmentmentioning
confidence: 97%
“…where ΔT is a reference temperature introduced to normalize the physical temperature, i.e., and Γ t should be adjusted to constrain η D in a reasonable range, e.g, 0.501 < η D < 2.0 [31][32][33][34][35][36]. Two numerical tests will be presented in the beginning of Section 5 to validate the scaling strategy in the LB modeling.…”
Section: Scaling Between the Physical And Lb Unit Systemsmentioning
confidence: 99%